Decoding academic success: the role of lecturers' teaching styles and students' motivation - Sembiring, Dinaria; Ginting, Bena; Tarigan, Hermelina Ekasari Br (Institute of Computer Science (IOCS), 2025)
This study examines the impact of Lecturer's Teaching Style and Learning Motivation on Student Learning Achievement in higher education. The motivation behind this research stems from the need to understand how teaching methods and student motivation collectively influence academic performance, especially in the context of modern learning environments. The research employed a quantitative approach using multiple linear regression analysis to analyze data from 51 students. The findings indicate that both Lecturer's Teaching Style (β = 0.554, p = 0.028) and Learning Motivation (β = 0.342, p = 0.036) significantly affect Student Learning Achievement, with Lecturer's Teaching Style showing a slightly stronger influence. These results suggest that enhancing teaching strategies and fostering student motivation can improve academic outcomes. The study underscores the importance of adapting teaching methods to diverse learning needs and creating a motivating learning environment to boost student performance. Educational institutions are encouraged to invest in training programs for lecturers and strategies to enhance student motivation. Future studies may explore additional factors influencing student achievement, such as self-regulation and socio-cultural aspects.